ANALISIS MODEL FRAUD HEXAGON DALAM MENDETEKSI POTENSI KECURANGAN LAPORAN KEUANGAN PADA PERUSAHAAN BUMN : ANALYSIS OF FRAUD HEXAGON TO DETECT FRAUD ON FINANCIAL STATEMENT - Sakina Sumbari; Kamaliah Kamaliah; Ruhul Fitrios (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2023)
The purpose of this study was to determine the effect of stimulus, opportunity, rationalization, ability, ego, coalition on fraudulent financial statements. The population in this study are state-owned companies listed on the IDX for 2016-2020. Sampling using purposive side. In order to obtain a sample of 12 companies. The type of data used is secondary data with documentation. Data analysis used logistic regression analysis. The results showed that stimulus, ego, coalition had a positive and significant effect on fraudulent financial statements, opportunity had a negative and significant effect on fraudulent financial statements, rationalization and ability had no effect on fraudulent financial statements